Effect of Annealing Time on Resistivity of Kenaf Fiber Modified Indium Zinc Oxide Prepared Via Dip Coating Process - Edynoor, O.; Warikh, A.R.M.; Moriga, T.; Murai, K.; Mohammad, E.; Salleh, M.R. (Journal of Advanced Manufacturing Technology (JAMT), 2017)
This paper reviewed the annealing time effect on resistivity of kenaf fiber modified indium zinc oxide (KF-IZO) as a functional material. Firstly, kenaf fiber (KF) had undergone alkaline surface treatment using Sodium Hydroxide (NaOH) solution with 5 % concentration. Dip coating process was applied in order to deposit amorphous IZO (In/Zn : 6.0 %) solution at room temperatures, 27ᵒC at 5 mm/s dipping rate. The thin film built up was annealed at 150ᵒC for 2, 4, 8 and 16 hours. Electrical resistivity was tested by Four Probe Method with copper attachment to determine the resistance of KF-IZO. As a result, KF-IZO with 4 hours annealing time showed the lowest resistivity with 0.12 Ω.mm while the highest resistivity 12.62 Ω.mm was shown by 16 hours annealing time. Surface morphology was observed under optical microscope, Scanning Electron Microscope (SEM) and SEMEDX to reveal coating distribution, elemental analysis and imperfection of KF-IZO. Moreover, the entire KF-IZO samples image illustrated revealed no significant fiber damages.